Distribution of Some Airborne Trace Elements in Aswan City - S.M. Hassan, Fatma (Asian Journal of Chemistry, 2010)
Rubidium, barium and strontium together with zirconium and neodymium have been investigated in Aswan dustfall in twelve experimental sites. To reveal the relative metal distribution throughout the Aswan area, a contour and isometric map for each metal has been drawn using an advanced mainframe computer programme. With the exception of barium, strontium and zirconium in a few sites, the level of the remaining metals (Rb & Nd) contamination of the Aswan topsoils is limited. This will perhaps be the case until the end of the next century, provided there is no major change in anthropogenic sources.